Safety of Use of Tantalum in Total Hip Arthroplasty. (4th March 2020) - Brüggemann, Anders; Mallmin, Hans; Bengtsson, Mats; Hailer, Nils P.
Abstract : Background: Tantalum implants have been used in >500, 000 orthopaedic patients. Although the risks of metallosis and aseptic lymphocyte-dominated vasculitis-associated lesions (ALVAL) after total hip arthroplasty (THA) are being debated, we are not aware of any studies investigating the liberation of tantalum ions and their potential effects on the immune system. We evaluated whether tantalum concentrations are elevated after THA with acetabular tantalum implants and assessed potential alterations in T-cell subpopulations. Methods: After a mean follow-up of 4 years (range, 0.5 to 8.9 years) of 144 patients who had undergone THA, blood samples were analyzed regarding blood tantalum concentrations, total white blood-cell counts, and lymphocyte subsets in 3 groups of patients: those treated with non-tantalum primary THA ("primary non-tantalum, " n = 30), those treated with primary THA with a tantalum cup ("primary tantalum, " n = 30), and those who underwent revision surgery with a tantalum shell ("revision tantalum, " n = 84). Blood donors served as controls for immunological parameters (n = 59). Correlations between tantalum concentrations and human leukocyte antigen (HLA)-DR + T cells were calculated, radiographic signs of implant loosening were assessed, and the Harris hip score (HHS) was used to evaluate hip function. Results: The median tantalum concentration was similar to the detection limit both in the primary non-tantalum group (0.05 µg/L, 95% confidence interval [CI] = 0.05 to 0.05 µg/L) and in the primary tantalum group (0.051 µg/L, 95% CI = 0.050 to 0.055 µg/L), and it was 0.091 µg/L (95% CI = 0.083 to 0.112 µg/L) in the revision tantalum group (p < 0.0001 in the group-wise comparison with both primary non-tantalum and primary tantalum). We found a weak negative correlation of higher tantalum concentration with the concentration of HLA-DR + /CD8 + T cells (r = −0.22, 95% CI = −0.35 to −0.05, p = 0.01) but no correlation of tantalum concentration with the concentration of HLA-DR + /CD4 + T cells (r = −0.11, 95% CI = −0.27 to 0.06, p = 0.24). The values for all lymphocyte subgroups were within normal ranges. No implants were deemed loose. The median HHS was good to excellent. Conclusions: Exposure to stable tantalum cups is associated with low blood concentrations of tantalum. Signs of T-cell activation typical of ALVAL seem to be lacking. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.